Process yield, proximate and chemical composition and antioxidant activity of astaxanthin from solenocera crassicornis (Funded Work) - Venkatesh Kuncham; Kandra Prameela; Kandra Prameela (International Journal of Pharma and Bio Sciences, 2020)
Aquaculture is the major source of several organisms in Indian resources. Coastal aquaculture is rich in natural resources with several species. Shrimp is one of the major aquacultural food and is processed by separating meat from head and carapace. The head and carapace is treated as shrimp waste. Generation of huge amounts of waste and dumping into the environment is a real nuisance to the public since putrification starts immediately after dumping of the waste. Shrimp waste is rich of natural valuable compounds. Solenocera crassicornis is a very rare shrimp found at a 40m of sea depth . In the present study we attempted to know the process yield, proximate and chemical composition and antioxidant activity of astaxanthin extracted from S.crassicornis. The frozen shrimps were thawed, peeled manually by separating meat from head and carapace (waste). The waste was homogenized in a laboratory mixer. The material was vacuum packed in polyethylene bags and kept at -20°C until further use. The total antioxidant activity of extracted astaxanthin from S. crassicornis was determined by using FRAP method where the reducing property of ferric ions with extracted astaxanthin was determined by taking different concentrations (10 to 100 µg/ml). High amount of waste in the form of head (75%) and carapace (82%) was observed when compared to the meat. Astaxanthin content is high in head (73.5%) and carapace (65.2%) compared to the meat. The scavenging activity has shown higher DPPH activity similar to Quercetin (80%). The IC 50 values of 265 µg/ml was observed for astaxanthin extracted from S. crassicornis. Low chitin (0.9%) content and high protein ( 15.5%) content was observed in the meat part. These results indicate that significant (P≤0.05) difference was found between different body components of S.crassicornis.